In Nasal Mucosal Secretions, Distinct IFN and IgA Responses Are Found in Severe and Mild SARS-CoV-2 Infection - Santos, Juliana de Melo Batista dos; Soares, Camila Pereira; Monteiro, Fernanda Rodrigues; Mello, Ralyria; Amaral, Jonatas Bussador do; Aguiar, Andressa Simões; Soledade, Mariana Pereira; Sucupira, Carolina; De Paulis, Milena; Andrade, Juliana Bannwart; Almeida, Flavia Jaqueline; Sáfadi, Marco Aurélio Palazzi; et al. (Frontiers in Immunology, 2021)
Likely as in other viral respiratory diseases, SARS-CoV-2 elicit a local immune response, which includes production and releasing of both cytokines and secretory immunoglobulin (SIgA). Therefore, in this study, we investigated the levels of specific-SIgA for SARS-CoV-2 and cytokines in the airways mucosa 37 patients who were suspected of COVID-19. According to the RT-PCR results, the patients were separated into three groups: negative for COVID-19 and other viruses (NEGS, n=5); negative for COVID-19 but positive for the presence of other viruses (OTHERS, n=5); and the positive for COVID-19 (COVID-19, n=27). Higher specific-SIgA for SARS-CoV-2, IFN-β, and IFN-γ were found in the COVID-19 group than in the other groups. Increased IL-12p70 levels were observed in OTHERS group as compared to COVID-19 group. When the COVID-19 group was sub stratified according to the illness severity, significant differences and correlations were found for the same parameters described above comparing severe COVID-19 to the mild COVID-19 group and other non-COVID-19 groups. For the first time, significant differences are shown in the airway’s mucosa immune responses in different groups of patients with or without respiratory SARS-CoV-2 infection.